Water Quality Analysis of Kalidami River Surabaya City Using Biomonitoring Method - Falaah, Daffa Dwi; Wardhana, Varrel Raffalino (Faculty of Civil Engeneering and Planning - ITATS, 2025)
Kalidami River in Surabaya is under heavy pollution pressure due to domestic and industrial activities, so a biomonitoring-based water quality assessment is needed. This study aims to analyze the condition of the river ecosystem through physical, chemical, and biological parameters. Water and sediment sampling was conducted in three river segments in April 2025. Physical-chemical parameters including BOD, COD, pH, temperature, TDS, and turbidity were measured using standard tools, while biological analysis focused on macroinvertebrates as bioindicators using the Shannon-Wiener Diversity Index (H') method. Results showed BOD (9.08-11.02 mg/L) and COD (61.3-82.6 mg/L) values exceeded the class 3 quality standard of PP No. 22 of 2021, indicating high organic pollution from domestic and industrial effluents. Although pH (7.53-7.55), temperature (29.9°C), and TDS (337-511 mg/L) met the standards, turbidity in Segment 1 reached 24.39 NTU. Macroinvertebrate diversity was low (H'=0.3768-0.6759) with pollution-tolerant species such as Tubificidae and Gambusia affinis dominating. This condition reflects the heavy ecological pressure due to waste accumulation, slow flow, and massive anthropogenic activities around the river. The study concluded that the degradation of the Kalidami River ecosystem requires immediate intervention, including structured waste management, community education, and periodic biomonitoring-based monitoring for sustainable restoration.